(untitled) (Medical Forum Monthly, 2021)
Objective: The practice of digoxin in patients having a trial fibrillation (AF) with heart failure and deprived of heart failure has not been discussed. The purpose of this analysis was to investigate the effect of digoxin therapy on frequency of mortality stratified by heart failure. Study Design: prospective / observational study Place and Duration of Study: This study was conducted at the Chaudhary Pervaiz Elahi Institute of Cardiology, Multan, Pakistan. Patients included from January 2020 to January 2021 and were enrolled for a year. Materials and Methods: This study encompassed 610 patients of atrial fibrillation. The analyzes were achieved using multivariate and univariate statistics. Results: The study included 610 patients. 46 + 11 years was the patients mean age. At discharge from hospital, 34% (n = 214) of patients were prescribed digoxin and among 48% (n = 103) have heart failure. Discharged 75 (12.3%) patients died after 1year of follow-up. Patients with heart failure had higher mortality at one month (4.2% vs 2.0% without HF; p <0.001), at 6 months (12.1% vs 4.3 without HF%; p <0.001) and at 12 months (23.4% vs 6.9 without HF%; p <0.001).When stratified digoxin therapy showed significantly higher mortality at one-year in patients with heart failure (at 12-month (24.1% vs 11.1% without HF and at 6-months 11.1% vs 7.9% without HF). Conclusion: In heart failure and atrial fibrillation patients, survival did not improve by digoxin. Though, in subjects deprived of heart failure, treatment with digoxin was related with significantly long-standing mortality.